Implementasi Program Penanggulangan Penyakit Demam Berdarah Dengue di Kecamatan Karawang Barat Kabupaten Karawang Tahun 2019 - Muhamad Iman Tawakal; Gili Argenti; Rudyk Nababan (Universitas Warmadewa, 2022)
Among the factors in seeing the success of public policy is health. Until now, one of the health problems that is still a problem in Indonesia is Dengue Hemorrhagic Fever (DHF). DHF is a disease caused by dengue virus infection and is transmitted through the Aedes aegypti mosquito. The Karawang Regency Government, in this case the Health Office, has done various things in tackling this disease, but there are still some shortcomings, including low public awareness about the importance of preventing and overcoming dengue fever, especially in West Karawang District, which is represented by the Karawang Kulon Health Center and Nagasari Health Center. . The focus of this research began in 2019 – 2020 using descriptive methods and qualitative approaches. Data collection techniques were carried out by library research, interviews, observations, and documentation. Data were taken from informants who were determined based on purposive sampling technique. Informants in this study, namely the Head of the Karawang Kulon Health Center and the Head of the Nagasari Health Center as well as one employee and one community member who felt the program from each Puskesmas. This study uses the theory of the policy implementation process according to Rondinelli with four variables that can affect the performance of a program, namely (1) environmental conditions; (2) inter-organizational relations; (3) organizational resources; (4) characteristics and capabilities of implementing agencies. Based on the facts in the field, it shows that the implementation of the DHF disease control program in West Karawang District is generally optimal, but there are several obstacles, especially organizational resource indicators.